2014
DOI: 10.1111/codi.12290
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and normal colorectal mucosa–adenomatous polyp–adenocarcinoma sequence: a meta‐analysis of 27 case–control studies

Abstract: The meta-analysis suggests a promoting effect of Helicobacter pylori on the risk of adenocarcinoma. It also suggests that Helicobacter infection might have its influence at the start of the adenomatous polyp disease sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
2
23
1
2
Order By: Relevance
“…However, whereas a previous study showed that duodenal ulcer was associated with decreased risk of gastric cancer [43], we found an increased risk for both gastric and duodenal ulcer patients. Our risk estimates for colon cancer were in agreement with studies reporting a modest increased risk of 20% [33]. The decreased risk of rectal cancer may reflect diagnosis of prevalent cancers during lower endoscopy following bleeding among patients with ulcer disease (vs. no screening in the general population).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, whereas a previous study showed that duodenal ulcer was associated with decreased risk of gastric cancer [43], we found an increased risk for both gastric and duodenal ulcer patients. Our risk estimates for colon cancer were in agreement with studies reporting a modest increased risk of 20% [33]. The decreased risk of rectal cancer may reflect diagnosis of prevalent cancers during lower endoscopy following bleeding among patients with ulcer disease (vs. no screening in the general population).…”
Section: Discussionsupporting
confidence: 88%
“…The association with gastric adenocarcinoma appears to be restricted to increased risk of noncardia cancer [31]. In contrast, H. pylori infection is associated with an increased risk of colorectal cancer [9,[32][33][34]. Finally, evidence to support an association with other nongastric GI cancers is sparse, and null associations have been reported [8,[35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…These precancerous lesions occur in the following order: gastritis, atrophy, intestinal metaplasia (IM), and eventually dysplasia. H. pylori represent the most significant risk factor for gastric malignant tumors (Wang et al, 2014). Gastric cancer (GC) is an insidious disease, with symptoms that often manifest at an advanced stage, a time when the few remaining therapeutic options have low efficiency (Boreiri et al, 2013).…”
Section: H Pylori Adhesion and Invasion Mechanismmentioning
confidence: 99%
“…Gastric cancer (GC) is an insidious disease, with symptoms that often manifest at an advanced stage, a time when the few remaining therapeutic options have low efficiency (Boreiri et al, 2013). Approximately 10% of infected individuals develop severe gastric lesions, such as those in peptic ulcer disease; 1-3% progress to GC, with a low 5-year survival rate, and 0-1% develop mucosa-associated lymphoid tissue (MALT) lymphoma (Parreira et al, 2013;Wang et al, 2014).…”
Section: H Pylori Adhesion and Invasion Mechanismmentioning
confidence: 99%
“…Подобные результаты продемонстрированы и в другом метаана-лизе F. Wang и соавт. [35] с выявленной связью между патогенны-ми штаммами H. pylori (CagA+) и колоректальной аденокарцино-мой (ОШ 1,22 при 95% ДИ от 1,08 до 1,37; р=0,05). В настоящее время единственной, подтвержденной на экспериментальном уровне, является патогенетическая гипотеза о взаимосвязи ги-пергастринемии на фоне ассоциированного с H. pylori атрофиче-ского гастрита и повышения пролиферативной активности коло-ноцитов [36,37].…”
Section: терапевтический архив 8 2015unclassified